The Right to a Fair Trial and Combatting Terrorism: The Case of Indonesia - Paripurna, Amira (Indonesian Journal of International Law, 2011)
After the 9/11 attack, the US government called upon global war on terror (GWOT). Then terrorism has been considered as a threat of global security. It is, therefore, has led both national and international concern under US hegemony. Furthermore, it has affected the proliferation of many national counter-terrorism laws. The terrorist attacks have threatened Indonesia over years. Under the act No.15/2003 jo No.1/Prp/2002 the Indonesian government has successfully conducted prosecutions to the terrorism perpetrators. However, it is identified that there are such violations regarding to international human rights rules and standards. The concern in handling terrorism demands a balance concern between security treatments and human rights. Thus, the challenge’s today are how to maintain the rights to a fair trial for every accused, the safeguard against abuse of power and the commitment of international community to human rights, while also preserving the capacity to national and international security concerns. The article 14 of International Covenant on Civil and Political Rights (ICCPR) enshrines a norm of International Human Rights law which protects individual from the unlawful and arbitrary curtailment of other basic rights and freedoms (a fair trial), which the most prominent are the rights to life and liberty of the person. The civil and political rights are categorized as non-derogable rights, it means that any derogation measures inconsistent with the State’s other obligations under international human rights law is prohibited. Thus, this paper aims to discuss whether and to what extent the right to a fair trial may be compromised in the name of security? Does the fair trial standard can be sacrificed to prosecute terrorism?